Micro Task Evaluation of Analog Vs. Digital Power Plant Control Room Interfaces. (September 2016) - Hildebrandt, Michael; Fernandes, Alexandra
There is a need for efficient and transparent human performance measurement methods to support interface evaluation for control room modernization projects. This paper presents experiences from the second pilot test of a micro task method developed to support this need. We benchmarked performance with analog control boards in a nuclear power plant control room simulator against performance with a modern overview display. Within 2.5 hours of simulator time and with 16 licensed operators as participants, we collected data for 1152 micro task questions, recording response time and accuracy for each question. The paper describes the study methodology and results, and draws conclusions about the future use of the micro task method for evaluation and training.